Is parental anxiety related to child anxiety? Insights from a four-wave longitudinal study in a Chinese context - Shek, Daniel T. L.; Li, Xiang; Yang, Banglin; Yang, Jiangfeng (Frontiers in Psychiatry, 2025)
ObjectiveThere has been a growing concern regarding the development of parental anxiety and child anxiety. However, the dynamic bidirectional relationship between parental anxiety and child anxiety remains unclear, particularly across different genders and developmental stages. This study investigated the bidirectional relationships between parental anxiety and child anxiety, and further explored the relationships across gender and age.MethodsData were collected across four waves from 2019 to 2022 in Sichuan Province, China, including 6,117 students (49.00% girls; 61.10% adolescents; M = 10.32 years, SD = 2.14). Parental anxiety was evaluated by the Self-Rating Anxiety Scale (SAS), and child anxiety was assessed using the Screen for Child Anxiety-Related Emotional Disorders (SCARED). A random intercept cross-lagged panel model (RI-CLPM) was constructed to distinguish between within- and between-person levels of parental anxiety and child anxiety.ResultsResults found that parental anxiety significantly predicted child anxiety across all time points, which supports the “parent effects” model. Meanwhile, child anxiety also influenced parental anxiety from Time 3 to Time 4, partially supporting the “reciprocal effects” model. Moreover, the impact of parental anxiety on girls’ anxiety was significantly stronger than on boys, and parental anxiety had a more substantial influence on children than on adolescents.ConclusionThese findings underscore the distinct roles of gender and developmental stages in the transmission of parental anxiety to children. The present findings provide theoretical and practical evidence for the development of parental anxiety and child anxiety in the Chinese context.